Effect of BaO Content on the Photoluminescence Properties of Mn2+ and Eu2+-Codoped Sr3−xBaxMgSi2O8 Phosphors - Shu-Han Liao; Fang-Tzu Hsu; Cheng-Fu Yang; Kao-Wei Min (Inorganics, 2025)
In this study, Mn2+ and Eu2+-codoped Sr3−xBaxMgSi2O8 (x = 0–1.5) phosphors were synthesized at 1400 °C under a reducing atmosphere composed of 5% H2 and 95% N2 to produce materials with blue light emission. The resulting powders were characterized using several analytical techniques: X-ray diffraction (XRD) was employed to identify the crystalline phases, scanning electron microscopy (SEM) was used to observe the microstructure, and photoluminescence excitation (PLE) and emission (PL) spectra were measured using a fluorescence spectrophotometer. The results revealed several key findings. XRD analysis showed that the Sr3MgSi2O8 (Sr3−xBaxMgSi2O8) phase coexisted with secondary phases of Sr2SiO4 and Sr2MgSi2O7. SEM observations indicated that the synthesized powders exhibited a distinctive needle-like structure anchored on the surfaces of the particles. The PL and PLE intensities increased sharply as the BaO content increased from x = 0 to x = 0.6, followed by a more gradual increase, reaching a peak at x = 1.2. Additionally, as the value of x increased, the wavelengths corresponding to maximum PL and PLE intensities exhibited a blue shift, moving to shorter wavelengths. Further investigation focused on the excitation behavior by replotting the PLE spectra using energy (eV) as the x-axis. A Gaussian fitting function was applied to deconvolute the excitation bands, enabling an in-depth analysis of how compositional variations influenced the Stokes shift.